PERAMALAN INDEKS HARGA PERDAGANGAN BESAR KELOMPOK KOMODITAS PERTANIAN MENGGUNAKAN METODE SINGULAR SPECTRUM ANALYSIS - SUKSEMAWAN, I MADE PRABA ESHA; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 13 No 2 (2024), 2024)
The wholesale price index (WPI) is an index used to measure the average price change over time of a package of goods in wholesale trade. This price index is an indicator to view general economic developments and material for market and monetary analysis. Related to WPI as material for market and monetary analysis, forecasting of WPI is very much needed, especially in agricultural commodities, which are a vital sector. The WPI in the agricultural commodity group in this study was forecasted using the singular spectrum analysis (SSA) method. The data used in forecasting is WPI data from January 2005 to December 2022. Forecasting accuracy level is determined by using vector singular spectrum analysis (VSSA) method. Forecasting results show that the best SSA model is obtained with the window length value  and MAPE value is 1,9%. This shows that the SSA method can predict the WPI of agricultural commodities very accurately.